THE DEPICTION OF CAPITALIST IN SORRY TO BOTHER YOU MOVIE - Sunaryo, Ayo; Juanda, Juanda (Universitas Negeri Semarang, 2020)
A movie as development of literature technique which according to Marxism is part of superstructure derives from the social process. Karl Marx himself divides society into two different groups: a capitalist class and a proletarian class. A capitalist who owns a mode of production has control over a proletariat whose life depends on the sale of labor to capitalists. This often leads to class conflict. That phenomenon also reflected in Sorry to Bother You, an American movie produced in 2018 and directed by Boots Riley, as data source used in this study. The story revolves around the struggle of a character named Cassius Green who works in Regalview, a telemarketing company. After being promoted, he faces a big company named Worryfree as his client. Later on, he revealed the cruelty of Worryfree owner that triggering him and another worker to fight the company. Thus, the objective of this research is to find out how a capitalist is being depicted in Sorry to Bother You movie. The research analyzed using a qualitative method also using Marxism and cinematography theory. The result indicates that the movie portrays the capitalist not only as a rich man but also manipulative as he changes the worker into a people-horse creature to produce cheap and strong labor. Besides, he is backed by the government despite condemned for slave labor. The conclusion from such depictions proves that the capitalist will do anything to gain profit even though he must exploit the workers.